Improvement of phytoplasma diagnostic techniques - Aljafer, Naofel (2016)
Phytoplasmas are wall-less, non-culturable, phloem-limited bacterial pathogens that belong to the Mollicutes. They cause many diseases in lots of plant species (wild and cultivated) belonging to many different plant families, resulting in significant losses in important crops, and economically damaging epidemics worldwide. Phytoplasmas infect major cultivated crops such as many annual crops, fruit trees, grapevines and palms, which makes control of these diseases a priority, and the first important step for management is efficient and effective phytoplasma diagnosis. Detection of phytoplasmas is difficult because of their irregular distribution within the diseased plants and low concentration inside infected plants. In the last two decades most research toward the detection of phytoplasmas has used nucleic acid-based techniques such as PCR, which is used to amplify regions of phytoplasma genomes existing inside infected plants. However, most routine diagnostics has moved from general PCR to real-time PCR, due to the improved sensitivity and reduced risk of contamination due to the use of a closed system for product detection. Also the method can be developed into a semi-quantitative method. In this project the aim has been to improve the specificity and reliability of phytoplasma diagnostic techniques by using primers that detect specific genes in phytoplasma genomes, and designing new universal primers for conventional and real-time PCR. This has involved developing new assays for 16Sr groups II, III, V, VI, XI, and XII, to facilitate analysis of changes in levels of different phytoplasmas in mixed infections. In addition, this work has involved the evaluation of LAMP (loop mediated isothermal amplification) diagnostic assays for different phytoplasma groups (I, II, III, V, VI, X, and XII) and also validating a rapid DNA extraction method and whether this is effective for all plant species (i.e. Madagascan periwinkle versus Napier grass and other grasses). The second main objective was to investigate the rate of evolution of phytoplasma genomes. For this, infected plants (of phytoplasma groups 16SrI, II, III, VI, and X) were grafted onto fresh plants at 3-4 month intervals throughout the project. Once the phytoplasma had re-established, DNA was extracted and a range of genes including 16S rRNA, secA, tuf, and rp were amplified and sequenced. The aim was to determine whether there was any evidence of genome evolution over time. However, the results suggested that in these genes at least, the rate of change due to point mutations and/or insertion of potential mobile elements (PMUs) was slow, with no sequence changes being detected over the three years of study.